Advances in Wound Management. Issue 23 (1st December 2018) - Rosenbaum, Andrew J.; Banerjee, Samik; Rezak, Kristen M.; Uhl, Richard L.
Abstract : Wound management is a notable healthcare and financial burden, accounting for >$10 billion in annual healthcare spending in the United States. A multidisciplinary approach involving orthopaedic and plastic surgeons, wound care nursing, and medical and support staff is often necessary to improve outcomes. Orthopaedic surgeons must be familiar with the fundamental principles and evidenced-based concepts for the management of acute and chronic wounds. Knowledge of surgical dressings, negative pressure wound therapy, tissue expanders, dermal apposition, biologics, and extracellular matrices can aide practitioners in optimizing wound care.